To solve this system of equations, we can use the method of substitution.
Step 1: Solve the first equation for x:
x - 2y = 6
x = 2y + 6
Step 2: Substitute the value of x in the second equation using the expression we found in step 1:
3(2y + 6) - 6y = 18
6y + 18 - 6y = 18
0y + 18 = 18
18 = 18
Step 3: Simplify the equation obtained in step 2:
0y + 18 = 18
18 = 18
Step 4: Since the equation in step 3 is always true, this means that the system of equations has infinitely many solutions. In other words, any value of y will satisfy the system.
Therefore, this system of equations does not have a unique solution.
solve the following system of equations
x - 2y = 6
3x - 6y = 18
1 answer